The Influence of Playdough on Increasing Fine Motoric Movement in the Fingers of 5 Year Old Children at Ar-Ruhama' Kindergarten and Independent Pkk Kindergarten, Patokan Village, Bantaran District, Probolinggo Regency - Tauriana; Retno Palupi Yonni Siwi (Universitas STRADA Indonesia, 2023)
One aspect of development that is very important to be developed in kindergarten is the ability of fine motor movements. Fine motor movements are body movements that use small muscles or fine muscle are related to the activity of putting or holding an object using the fingers. To analyze the effect of playing playdough media in on the improvement of fine motor movements in the fingers of children aged 5 years in Ar-Ruhama’ Kindergarten and PKK Mandiri Kindergarten, Patokan Village Bantaran District Regency Probolinggo. The study use a Quasy Experimental design with a pretest and posttest control group design. The sample in this study was 64 respondents consisting of 32 control groups and 32 intervention groups with Purposive sampling technique. This research was conducted for 4 consecutive days within 25 minutes and the measurement of the level of fine motor achievement was using an observation sheets. In the intervention group, before being given playing playdough media, they were first given a pretest and then given a posttest week, but the control group was not given playdough playing media intervention. This study use the Wilcoxon test.The results of statistical test in the intervention group obtained a e p value was 0.002 (<0.05) Ha was accepted,this means that there is an influence of playdough playing media on the improvement of fine motor movements in the fingers of preschool-aged children (5 years). There is an Effect of Playing playdough media on the improvement of fine motor movements in the fingers of children aged 5 years in Ar-Ruhama’ Kindergarten and PKK Mandiri Kindergarten, Patokan Village Bantaran District Regency Probolinggo.